Leadership Style and Employee Motivation: Unveiling the Key to Productivity in Fast-Food Restaurants - Kaputri, Evanny; Lukita, Fiona; Onesis, Jennifer; Juliana, Juliana; Pramezwary, Amelda (Center for Research and Community Service (LPPM) University of Abulyatama, 2025)
Leadership style significantly influences employee motivation, particularly in fast-food restaurants, where high-paced environments and repetitive tasks impact job satisfaction and performance. This study examines the relationship between leadership styles and employee motivation in fast-food restaurants. A quantitative survey was conducted with 113 employees using convenience sampling from various fast-food outlets to assess their perceptions of leadership effectiveness and Motivation. Data were analyzed using descriptive and inferential statistical methods. The findings indicate that Leadership style has the most substantial positive effect on employee motivation, fostering inspiration, recognition, and professional growth. These results highlight the importance of adopting a balanced leadership approach to enhance employee motivation and productivity in fast-food establishments. The study offers valuable insights for managers seeking to improve employee engagement and retention in the service industry.